A research in Quran Islamic indicator minaret themes Inscription in Iran - zahra Poorshabanian (قرآن فرهنگ و تمدن)
Minaret will be considered as a one of the most important buildings among all kinds of Islamic buildings, in historical and cultural and architectural point. This architectural symbol passed with conductor function, Azan Station and various victory revolution symbol in form and decorating. Muslim artists done various decorating like inscription on minarets. These inscriptions as alive historical documents will show indicator concepts from form, decorating, condition, founders and materials which used in minaret. One of the most important section in inscription minarets is Quranic decoration. Now the question is that what is the aim of Muslim architects for using Quranic verses and glory names in inscription? On the base of above question aim of now research is that using from descriptive and analytical procedure and with relying on study sources and checking field to introduce and analyzing themes of Quranic inscriptions of Iranian minarets that answering to said question will be simple. we can see outcome of this research on showing face as a signs of God, Quranic themes with monotheism concept and various buildings like united collection.